A pseudotumoral form of Crohn's disease: A case report and review of the literature - Meriem Sabbah; Ghada Gharbi; Raja Jouini; Dhafer Haddad; Norsaf Bibani; Chiraz Chamakhi; Dalila Gargouri (Clinical Case Reports, 2021)
Abstract In front of a colonic tumor, the diagnosis of a pseudotumoral form of Crohn's disease must be considered. However, it is a rare form, especially when inaugural and a neoplasia must be eliminated before retaining the diagnosis.